Perspective Paper – Cultural and Religious Heritage of Servant Leadership in India - Dipanwita Biswas; Seema Singh; Sunil K. Verma (Colombo Business Journal)
Servant Leadership is a contemporary philosophy of leadership suggesting that the most effective leaders serve those around them. It is a philosophy emphasising the prioritisation of serving others over oneself and is particularly aligned with non-Western traditions, especially in India. Servant leadership is interpreted and practised variably in Western and non-Western contexts, mirroring the cultural values and philosophical traditions inherent to these countries. This paper aims to illustrate the presence of a non-Western perspective of servant leadership within the religious doctrines and practices of Hinduism, Buddhism and Sikhism in India. In contrast to Western models that prioritise individual empowerment and organisational achievement, the Indian perspective is profoundly rooted in the nation’s spiritual, religious, and cultural heritage, offering significant insights for global leadership practices in an increasingly interconnected world. Future studies may investigate the integration of indigenous leadership concepts into modern global leadership frameworks.